Restored tallgrass prairies have reduced phylogenetic diversity compared with remnants. Issue 4 (10th March 2017) - Barak, Rebecca S.; Williams, Evelyn W.; Hipp, Andrew L.; Bowles, Marlin L.; Carr, Gabriela M.; Sherman, Robert; Larkin, Daniel J.
Summary: Ecological restoration is critical for mitigating habitat loss and providing ecosystem services. However, restorations often have lower diversity than remnant, reference sites. Phylogenetic diversity is an important component of biodiversity and ecosystem function that has only recently been used to evaluate restoration outcomes. To move towards prediction in the restoration of biodiversity, it is necessary to understand how phylogenetic diversity of restorations compares with that of reference sites, and where deficits are found, to evaluate factors constraining phylogenetic diversity. We quantified plant taxonomic and phylogenetic diversity in eastern tallgrass prairie, one of the most endangered ecosystems on earth. We measured diversity at large (site) and small (plot) scales in 19 restored prairies and compared patterns with those from 41 remnant prairies. To evaluate how environmental conditions and management actions influence outcomes, we tested the effects of soil properties and seed mix composition on diversity of restorations. Restored prairies were less phylogenetically diverse than remnants at both spatial scales. On the other hand, the total species richness of remnant and restored prairies did not significantly differ, but remnants had higher native richness. Restored communities were taxonomically and phylogenetically distinct from remnants. Soil properties (moisture and pH) influenced phylogenetic diversity and composition. There were positive relationships between the taxonomic and phylogenetic diversity of seed mixes and resulting diversity of planted assemblages (excluding volunteer species). Species in seed mixes were more closely related than expected by chance, and several clades found in remnant prairies were missing from seed mixes. Synthesis and applications . Restored tallgrass prairies had lower phylogenetic diversity than remnant prairies, which may contribute to the widely observed phenomenon of restorations not being functionally equivalent to reference sites. It is encouraging for restoration efforts that seed mix phylogenetic diversity predicted phylogenetic diversity of planted assemblages. This indicates that designing phylogenetically diverse seed mixes for restoration is beneficial. In addition, clades found in reference sites that are missing from restoration seed mixes could be added to new or existing restorations to reduce gaps in phylogenetic diversity. Further work on the effects of management on phylogenetic diversity is needed to advance restoration of biodiversity. Abstract : Restored tallgrass prairies had lower phylogenetic diversity than remnant prairies, which may contribute to the widely observed phenomenon of restorations not being functionally equivalent to reference sites. It is encouraging for restoration efforts that seed mix phylogenetic diversity predicted phylogenetic diversity of planted assemblages. This indicates that designing phylogenetically diverse seed mixes for restoration is beneficial. In addition, clades found in reference sites that are missing from restoration seed mixes could be added to new or existing restorations to reduce gaps in phylogenetic diversity. Further work on the effects of management on phylogenetic diversity is needed to advance restoration of biodiversity.